Formation of 4'-carboxyl acid metabolite of imrecoxib by rat liver microsomes - Xu Hai-yan; Zhang Peng; Gong Ai-shen; Sun Yu-ming; Chu Feng-ming; Guo Zong-ru; Zhong Da-fang (Acta Pharmacologica Sinica, 2016)
Aim: Imrecoxib is a novel and moderately selective COX-2 inhibitor. The aim of the present in vitro investigation was to study the formation of the major metabolite 4'-carboxylic acid imrecoxib (M2) and identify the enzyme(s) involved in the reaction. Methods: The formation of M2 was studied in rat liver cytosol in the absence or presence of liver microsomes. The formed metabolite was identified and quantified by LC/MSn. In addition, to characterize the cytochrome P450 (CYP) isozymes involved in M2 formation, the effects of typical CYP inhibitors (such as ketoconazle, quinine, -naphthoflavone, methylpyrazole, and cimetidine) on the formation rate of M2 were investigated. Results: The formation of M2 from 4’- hydroxymethyl imrecoxib (M4) was completely dependent on rat liver microsomes and NADPH. Enzyme kinetic studies demonstrated that the formation rate of M2 conformed to monophasic Michaelis-Menten kinetics. Additional experiments showed that the formation of M2 was induced significantly by dexamethasone and lowered by ketoconazole strongly and concentration-dependently. By comparison, other CYP inhibitors, such as α-naphthoflavone, cimetidine, quinine, and methylpyrazole had no inhibitory effects on this metabolic pathway. Conclusion: These biotransformation studies of M4 and imrecoxib in rat liver at the subcellular level showed that the formation of M2 occurs in rat liver microsomes and is NADPH-dependent. The reaction was mainly catalyzed by CYP 3A in untreated rats and in dexamethasone-induced rats. Other CYP, such as CYP 1A, 2C, 2D, and 2E, seem unlikely to participate in this metabolic pathway.